Advantages of a novel in situ pH measurement for soilless media - Noah James Langenfeld; Hikari Ai Skabelund; Hikari Ai Skabelund; Royal Heins; Bruce Bugbee (Frontiers in Plant Science, 2024)
Rhizosphere pH determines nutrient bioavailability, but this pH is difficult to measure. Standard pH tests require adding water to growth media. This dilutes hydrogen ion activity and increases pH. We used a novel, in situ, pointed-tip electrode to estimate rhizosphere pH without dilution. Measurements from this electrode matched a research-grade pH meter in hydroponic nutrient solutions. We then compared measurements from this electrode to saturated paste and pour-through methods in peat moss, coconut coir, and pine bark. The pointed-tip electrode was unable to accurately measure pH in the highly-porous pine bark media. Adding deionized water to the other media at container capacity using the saturated paste method resulted in a pH that was 0.59 ± 0.30 units higher than the initial in situ measurement at the top of the container. This increase aligns with established solution chemistry principles. Measurements of pH using the pour-through method were 0.38 ± 0.24 pH units higher than in situ measurements at the bottom of the container. We conclude that in situ pH measurements are not subject to dilution and are thus more representative of the rhizosphere pH than the saturated paste and pour-through techniques.